Electrical spin injection in modulation-doped GaAs from an in situ gerown Fe/MgO layer - Shim, Seong Hoon; Kim, Hyung-jun; Koo, Hyun Cheol; Lee, Yun-Hi; Chang, Joonyeon (AMER INST PHYSICS, 2015)
We study spin accumulation in n-doped GaAs that were electrically injected from Fe via MgO using three-terminal Hanle measurement. The Fe/MgO/GaAs structures were prepared in a cluster molecular beam epitaxy that did not require the breaking of the vacuum. We found the crystal orientation relationship of epitaxial structures Fe[100]//MgO[110]//GaAs[110] without evident defects at the interface. Control of depletion width and interface resistance by means of modulation doping improves spin injection, leading to enhanced spin voltage (Delta V) of 6.3mV at 10K and 0.8mV even at 400 K. The extracted spin lifetime and spin diffusion length of GaAs are 220 ps and 0.77 mu m, respectively, at 200 K. MgO tunnel barrier grown in situ with modulation doping at the interface appears to be promising for spin injection into GaAs. (C) 2015 AIP Publishing LLC.
Keywords: TUNNEL-JUNCTIONS; ROOM-TEMPERATURE; MAGNETORESISTANCE; SILICON